PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP KEAKTIFAN DAN MINAT BELAJAR SISWA KELAS V SD INPRES HARTACO INDAH - Feren Pratiwi Pomalingo; Dyah Magfirah Chairunnisa; Nurbaya; Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the world of education, learning media is very necessary in an effort to increase students' understanding, knowledge and absorption of certain learning content so that the learning process becomes more interesting and optimal. This learning media is an important element in the learning process, so that students can more easily understand the content of the material presented by the teacher and increase student interest and activeness in learning. One learning media that can be used to increase student activity and interest in learning is Wordwall learning media. The aim of this research is to determine the effect of using Wordwall media on students' activeness and interest in learning. The method used is a quantitative approach with an ex-post facto type of research. The population and sample for this research are all fifth grade students at SD Inpres Hartaco Indah, totaling 33 students. The research results show that by implementing Wordwall-based learning media, students' activeness and interest in learning increases and they achieve the expected learning outcomes.